Gentelligence : the revolutionary approach to leading an intergenerational workforce - Gerhardt, Megan W.; Nachemson-Ekwall, Josephine, 1995-; Fogel, Brandon, 1996- (Rowman & Littlefield, 2021)
"No one needs another book about how to lead Millennials -- what we need is a book about harnessing the untapped potential from the diversity of thought in a multigenerational workforce. "Gentelligence" is that book. It presents a transformative way to end the generational wars once and for all"--